Physicians' Perspective on a Multidisciplinary Approach to Dysphagia Management - Bakhtiyari, Jalal (Iran J Otorhinolaryngol, 2019)
INTRODUCTION: Professionals need a multidisciplinary approach to manage oropharyngeal dysphagia (OPD). Each team member should be aware of the signs and symptoms of OPD and collaborate with other team members to reach an optimum outcome. This study aimed to evaluate the knowledge and attitude of Iranian physicians regarding dysphagia and speech and language therapy roles in the management of dysphagia. MATERIALS AND METHODS: In this nonexperimental descriptive study, 133 physicians filled a researcher-made questionnaire entailing three sections, each of which recorded the participants’ demographic information, OPD knowledge (23 items), and attitude toward OPD (5 items). RESULTS: Iranian physicians correctly answered 70.3% of the questions indicating that they had a moderate level of knowledge on OPD. However, only 53% of the physicians referred their patients to speech-language pathologists, and almost 50% of them reported a significant recovery after speech therapy in their patients. CONCLUSION: It seems that Iranian physicians need to adopt an interdisciplinary approach to manage OPD. Achievement of sufficient knowledge on the pathology of OPD, along with collaboration with other team members, can improve the outcome for patients with OPD.